Pengaruh Jumlah Produk Tayang, Letak Geografis dan Jumlah Penyedia terhadap Transaksi pada Platform Marketplace XYZ - BKL, Dhya Dhanussie; Nurjanah, Siti (Research and Community Service UNIVERSITAS KALBIS, 2024)
This study examines the influence of the number of displayed products, geographical location, and number of providers on transactions in the Platform Marketplace XYZ. Using documentation method, data from 2020 to 2022 were analyzed in depth. The results of descriptive analysis show a growth trend in the number of displayed products, providers, and transactions on the platform. Gorontalo province emerged as the region with the highest transaction value. This research provides insights into the factors affecting e-commerce transactions in Indonesia, particularly on the Platform Marketplace XYZ, and offers valuable insights for the development of more effective marketing strategies. It is hoped that the findings of this study can serve as a reference for other researchers in the field of e-commerce.